The Primacy of the Ecumenical Patriarch in the Ottoman Empire - Геча, Јов (Sabornost - The Theological Year-book, 2015)
With the fall of the Byzantine Empire, May 29th 1453, a new model of relationship will appear between the Church and the state within the ancient Roman empire in the East. Consequently, the system of the Pentarchy developed in the first millennium, will receive a different model at the Christian East, because it will be subordinated to the Ottoman yoke. The new model of relationship between the Church and the new Empire will reflect rapidly on the relations among the Eastern Patriarchs, also to the place and role of the primacy of Ecumenical Patriarch.